(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the political processes of the end of the ХХ - beginning of the ХХI century which promoted activization of the oral – speech discourses in the national language system. The accent was made on verbal freedom in a society, which promotes unjustified penetration of a slang by colloquial speech on pages of press, on TV, in radio and inevitably conducts to destruction of our spiritual - cultural space.